2008
DOI: 10.2215/cjn.01040308
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet HCl and Concurrent Low-dose Vitamin D Improves Treatment of Secondary Hyperparathyroidism in Dialysis Patients Compared with Vitamin D Alone

Abstract: Background and objectives: Patients with chronic kidney disease (CKD) receiving dialysis often develop secondary hyperparathyroidism with disturbed calcium and phosphorus metabolism. The National Kidney Foundation-Kidney Disease Outcomes Quality Initiative (KDOQI) was established to guide treatment practices for these disorders. The ACHIEVE study was designed to test two treatment strategies for achieving KDOQI goals.Design, setting, participants, measurements: Individuals on hemodialysis treated with vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 29 publications
6
118
0
2
Order By: Relevance
“…Several studies have reported the effect of cinacalcet on decreasing iPTH levels (1,4,5), with associations between cinacalcet administration and decreased iPTH levels in this study found to be consistent with those in randomized control studies (4,5) and a previous observational study (1). However, little is known about the effect of concomitant therapy with cinacalcet and VDRA (15), particularly with regard to the effect of VDRA dosage change in concomitant therapy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Several studies have reported the effect of cinacalcet on decreasing iPTH levels (1,4,5), with associations between cinacalcet administration and decreased iPTH levels in this study found to be consistent with those in randomized control studies (4,5) and a previous observational study (1). However, little is known about the effect of concomitant therapy with cinacalcet and VDRA (15), particularly with regard to the effect of VDRA dosage change in concomitant therapy.…”
Section: Discussionsupporting
confidence: 85%
“…Although a number of previous studies have reported that cinacalcet administration reduced levels of phosphorus and calcium (1,4,5,(7)(8)(9), few have examined the effects of concomitant therapy with VDRA. We found that a combination pattern involving starting cinacalcet and decreased VDRA was effective in achieving target levels of phosphorus and calcium.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the effects of treatment with Cinacalcet and calcitriol analogs on circulating FGF23 levels in ESRD patients, we measured FGF23 levels in participants of the ACHIEVE study, a randomized controlled clinical trial of HD patients with SHPT designed to test whether treatment with Cinacalcet plus lowdose calcitriol analogs (Cinacalcet-D) would compare with treatment with calcitriol analogs alone in (Flex-D) in attainment of National Kidney Foundation K/DOQI mineral metabolic parameters (25). In this secondary analysis, we used prospectively collected samples from a subset of participants to study change in FGF23 levels in response to the two treatment strategies.…”
mentioning
confidence: 99%
“…Cunningham et al [14] Meta-analysis of eight randomized, vitamin D alone (where flexible dosing was allowed) in 173 dialysis patients (ACHIEVE) [12]. In this study, the fixed combination of cinacalcet plus low-dose vitamin D resulted in an effective PTH lowering when compared to vitamin D alone.…”
Section: Studies Of Cinacalcet In Dialysis Patients With Shptmentioning
confidence: 86%